Differential gene expression in the insect pathogen Steinernema feltiae in response to chromium VI exposure in contaminated host cadavers. (October 2020) - Boyle, Stephen; Kakouli-Duarte, Thomais
Graphical abstract: Highlights: The insect pathogen Steinernema feltiae elicits a toxicological response to chromium VI contamination in vivo. We detected the expression of 4 gene families known, or suspected, to be linked to systematic response to toxic stress. These were glutamine synthetase, thioredoxin, interferon, and ATP synthetase subunit. Three other gene families were suspected to be expressed, though require further study to be confirmed. These are neurexin genes, RNA subunit genes and some form of nitrate assimilation homologues.